2005
DOI: 10.1021/jf050254+
|View full text |Cite
|
Sign up to set email alerts
|

Automated On-line Solid-Phase Extraction−Liquid Chromatography−Electrospray Tandem Mass Spectrometry Method for the Determination of Ochratoxin A in Wine and Beer

Abstract: An automated on-line solid-phase extraction-liquid chromatography-electrospray tandem mass spectrometry (SPE-LC-ESI-MS/MS) method was developed for the determination of ochratoxin A (OTA) in alcoholic beverages. Mean recoveries for wine and beer were, respectively, 75 and 82%. Detection was achieved in negative ionization with a Q TRAP mass spectrometer operating in multiple-reaction monitoring (MRM) mode or enhanced product ion (EPI) mode, using the third quadrupole as linear ion trap. The MRM mode turned out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 31 publications
(44 reference statements)
1
29
1
Order By: Relevance
“…In Italy, Visconti et al [147] found OTA in 30 out of 61 beer samples, with no substantial differences between strong and light beers. The results of Bacaloni et al [148] agreed with these data. In Germany, the first results were obtained with methods having a relatively high limit of detection, so consequently, the frequency of positive samples (42.5%) was low, although values as high as 1.53 ng/mL were reported.…”
Section: Occurrence Of Ota In Beersupporting
confidence: 60%
“…In Italy, Visconti et al [147] found OTA in 30 out of 61 beer samples, with no substantial differences between strong and light beers. The results of Bacaloni et al [148] agreed with these data. In Germany, the first results were obtained with methods having a relatively high limit of detection, so consequently, the frequency of positive samples (42.5%) was low, although values as high as 1.53 ng/mL were reported.…”
Section: Occurrence Of Ota In Beersupporting
confidence: 60%
“…As m/z 98.2 emerged in both fragmentation scans with the highest intensity, we chose it as the identification ion. At present, chromatographic separation followed by MRM detection of two ions can be used to precisely identify a molecule (Bacaloni et al 2005).…”
Section: Ms Settingsmentioning
confidence: 99%
“…Only a few methods have been developed for the analysis of food ingredients so far. Bacaloni et al (2005), as well as Newkirk et al (1998), investigated mycotoxins in wine, beer and corn-based feed. In nutraceuticals, ephedrine could be detected with automated SPE-HPLC (Stevens 2003).…”
Section: Introductionmentioning
confidence: 99%
“…HPLC with mass spectrometry detection (HPLC-MS) has also been proposed for the determination of OTA in wine and beer samples (LODs of about 0.003 ng mL −1 and measurement ranges of 0.01 to 1 ng mL −1 of OTA) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%